MENDing The Gap: A Resourceful Solution for Medical Equipment Management Disparity - Gordon, Rayonna (Wake Forest University, 2020)
Developing countries rely heavily on donated medical equipment from high income countries, which often challenges their limited resources, just to provide necessary and common medical attention. A team from Wake Forest Baptist Medical Center confirmed this situation during a two-week intensive investigation at AIC Kijabe Hospital in Kijabe, Kenya, who experience an average of over 10,000 reported issues each year, often leaving equipment to sit unused. Currently there is a gap in the communication network of maintenance and management systems at resource-limited facilities, like AIC Kijabe Hospital, hindering the monitoring and timely repair of medical equipment to help sustain good medical care. Our goal is to create a more comprehensive and organized record of equipment services, thereby improving communication and responsiveness. The Medical Equipment Network Documentation System (MENDS) provides a simple communication network for equipment servicing from failure to restoration using text messaging.
Keywords: Developing Countries; Documentation; Health Resources; Maintenance